La investigacion a nivel de finca en Ecuador - Cardoso, V.H.; Villasis, C. (International Center for Tropical Agriculture, 1987)
The methodology for on-farm research in Ecuador is characterized by the approach used in production systems and the work of a multi-disciplinary team. The objectives, methodology, and results obtained from the experience are described. Bean var. E- 1056, PI 311996, G 11820, E-605, and E-794 have been accepted by both producers and consumers. Several bean lines evaluated have been earlier than the local var. allowing growers to harvest other crops, that is, accomplish a better rotation of the soil. Bean var. E-101 is a good alternative for fresh consumption because of its large grains, shorter plant cycle, and tolerance to diseases in comparison with the local var. (CIAT)